Boosting ORR Catalytic Activity by Integrating Pyridine‐N Dopants, a High Degree of Graphitization, and Hierarchical Pores into a MOF‐Derived N‐Doped Carbon in a Tandem Synthesis. Issue 10 (24th April 2018) - Liu, Dandan; Li, Liangjun; Xu, Huanfei; Dai, Pengcheng; Wang, Ying; Gu, Xin; Yan, Liting; Zhao, Guoming; Zhao, Xuebo
Abstract: N‐doped carbon materials represent promising metal‐free electrocatalysts for the oxygen reduction reaction (ORR), the cathode reaction in fuel cells, metal–air batteries, and so on. A challenge for optimizing the ORR catalytic activities of these electrocatalysts is to tune their local structures and chemical compositions in a rational and controlled way that can achieve the synergistic function of each factor. Herein, we report a tandem synthetic strategy that integrates multiple contributing factors into an N‐doped carbon. With an N‐containing MOF (ZIF‐8) as the precursor, carbonization at higher temperatures leads to a higher degree of graphitization. Subsequent NH3 etching of this highly graphitic carbon enabled the introduction of a higher content of pyridine‐N sites and higher porosity. By optimizing these three factors, the resultant carbon materials displayed ORR activity that was far superior to that of carbon derived from a one‐step pyrolysis. The onset potential of 0.955 V versus a reversible hydrogen electrode (RHE) and the half‐wave potential of 0.835 V versus RHE are among the top ranks of metal‐free ORR catalysts and are comparable to commercial Pt/C (20 wt %) catalysts. Kinetic studies revealed lower H2 O2 yields, higher electron‐transfer numbers, and lower Tafel slopes for these carbon materials compared with that derived from a one‐step carbonization. These findings verify the effectiveness of this tandem synthetic strategy to enhance the ORR activity of N‐doped carbon materials. Abstract : Two steps to improvement : A new type of N‐doped carbon that integrates a high density of pyridine‐N active sites, a high degree of graphitization, and hierarchical porosity was fabricated by using a tandem synthetic technique for superior activity in the oxygen reduction reaction (see figure; Pyri‐N=pyridine‐N).